Simultaneous biological removal of nitrogen and phosphorus from secondary effluent of wastewater treatment plants by advanced treatment: A review - Qi Zhou; Sun, Haimeng; Jia, Lixia; Wu, Weizhong; Wang, Jianlong (CHEMOSPHERE, 2022)
With the advancement of water ecological protection and water control standard, it is the general trend to upgrade the wastewater treatment plants (WWTPs). The simultaneous removal of nitrogen and phosphorus is the key to improve the water quality of secondary effluent of WWTPs to prevent the eutrophication. Therefore, it is urgent to develop the applicable technologies for simultaneous biological removal of nitrogen and phosphorus from secondary effluent. In this review, the composition of secondary effluent from municipal WWTPs were briefly introduced firstly, then the three main treatment processes for simultaneous nitrogen and phosphorus removal, i.e., the enhanced denitrifying phosphorus removal filter, the pyrite-based autotrophic denitrification and the microalgae biological treatment system were summarized, their performances and mechanisms were analyzed. The influencing factors and microbial community structure were discussed. The advanced removal of nitrogen and phosphorus by different technologies were also compared and summarized in terms of performance, operational characteristics, disadvantage and cost. Finally, the challenges and future prospects of simultaneous removal of nitrogen and phosphorus technologies for secondary effluent were proposed. This review will deepen to understand the principles and applications of the advanced removal of nitrogen and phosphorus and provide some valuable information for upgrading the treatment process of WWTPs.